Engaging the Ottoman Empire - O'Quinn, Daniel.
1 online resource (408 pages)
Keywords: Daniel O'Quinn investigates the complex interpersonal, political, and aesthetic relationships between Europeans and Ottomans in the long eighteenth century. Richly illustrated and provocatively argued, Engaging the Ottoman Empire demonstrates that study of the Ottoman world is vital to understanding European modernity.